Systemic evaluation of inclisiran on the risk of new-onset diabetes and hyperglycemia compared to evolocumab and atorvastatin - Li, Fei; Ye, Huan; Chen, Lingbin; Ma, Yuanchun; Chen, Sunhui (Frontiers in Pharmacology, 2025)
BackgroundInclisiran is an siRNA-based cholesterol-lowering drug with N-acetylgalactosamine carbohydrate (GalNAc) and is used for the treatment of hypercholesterolemia or dyslipidemia. It reduces LDL-C by 50%, with a convenient dosing schedule and fewer adverse events. Unlike statins, inclisiran has not been associated with an increased risk of muscle or liver adverse events in clinical studies. This favorable safety profile makes inclisiran a valuable alternative for patients who are intolerant of statins due to muscle or hepatic side effects. However, its impact on glycemic control and diabetes risk is unclear and understudied.Methods and resultsThe US Food and Drug Administration Adverse Event Reporting System (FAERS) study analyzed hyperglycemia and diabetes risks for inclisiran, atorvastatin, and evolocumab. Data from 2021 to 2024 were assessed for Medical Dictionary (MedDRA) terms, and SAS 9.4 with a reporting advantage ratio (ROR) and Bayesian credible interval progressive neural network (BCPNN) was used for analysis. Systematic review and meta-analysis were conducted using PubMed, Embase, and specific search terms. Two research workers extracted data independently, and the study quality was assessed with the Cochrane and Newcastle–Ottawa scales. RevMan 5.4 and Stata 18.0 were used for analyses. Ethical approval was waived due to the use of public, anonymous data. From 2015 Q1 to 2024 Q1, 12,821,285 adverse events were reported in FEARS, with 3,375 inclisiran, 126,620 evolocumab, and 42,228 atorvastatin cases. Atorvastatin had a higher ROR for type 2 diabetes (195.03) than inclisiran (0.95) and evolocumab, but it was not statistically significant. Glucose intolerance and blood glucose issues showed weak signals for inclisiran and atorvastatin. A literature search yielded 16 relevant articles, including six cohort studies and 10 RCTs, totaling 297,863 patients. The incidence of new-onset diabetes was higher with atorvastatin than with inclisiran, placebo, and evolocumab. The SUCRA rankings were atorvastatin > inclisiran > placebo > evolocumab for new diabetes incidence.ConclusionThe FAERS study and meta-analysis indicate that inclisiran may carry a lower risk of new-onset diabetes than atorvastatin, warranting further investigation into inclisiran’s impact on glycemic control.